2021
DOI: 10.2174/1573397116666200907112338
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Education on Cardiovascular Risk Factors in Rheumatoid Arthritis Patients

Abstract: Aim: The aim of this study was to investigate the effect of dietary education on cardiovascular risk factors in patients with rheumatoid arthritis. Method: In this randomized clinical trial, 112 patients with rheumatoid arthritis were randomly assigned into two groups, intervention and control. Dietary education was provided for the intervention group in 4 sessions; anthropometric measurements, serum levels of RF, triglycerides, cholesterol, HDL, LDL, and fasting blood sugar were measured before and three m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The results demonstrated significant improvement in blood lipid profile (triglycerides, HDL) and Apo-B100/Apo-A1 ratio, which are important markers of future CVD risk [146,147]. A randomized controlled study of 112 RA patients found that dietary education was associated with significant improvements in multiple traditional CVD risk factors (cholesterol, triglycerides, LDL, systolic and diastolic blood pressure) [148].…”
Section: Screening For Cvd In Inflammatory Arthritis and The Role Of ...mentioning
confidence: 95%
“…The results demonstrated significant improvement in blood lipid profile (triglycerides, HDL) and Apo-B100/Apo-A1 ratio, which are important markers of future CVD risk [146,147]. A randomized controlled study of 112 RA patients found that dietary education was associated with significant improvements in multiple traditional CVD risk factors (cholesterol, triglycerides, LDL, systolic and diastolic blood pressure) [148].…”
Section: Screening For Cvd In Inflammatory Arthritis and The Role Of ...mentioning
confidence: 95%